2000
DOI: 10.1111/j.1525-1373.2000.22410.x
|View full text |Cite
|
Sign up to set email alerts
|

Antisperm Antibodies Associated with Infertility: Properties and Encoding Genes of Target Antigens

Abstract: Abstract. Infertility among couples of reproductive age is a perplexing condition when the cause is indeterminate. These cases are classified as unexplained infertility. In a subset of subjects, antisperm antibodies with sperm agglutinating and/or immobilizing activities have been detected in the blood or fluids of the reproductive tract. These cases are designated as immunologic infertility although a cause and effect relationship of the antibodies to infertility has not been established. In this review, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 125 publications
(153 reference statements)
1
9
0
Order By: Relevance
“…Our findings are similar to those of Qu et al [38] in which injections of syngeneic testicular germ cells without adjuvants or bacterial components resulted in antibodies recognizing antigens of 15-200 kDa specific to round spermatids. Together, these findings may contribute to ongoing efforts to identify prominent germ cell antigens for use as diagnostic biomarkers or relevant targets for contraceptive vaccines [39,40].…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are similar to those of Qu et al [38] in which injections of syngeneic testicular germ cells without adjuvants or bacterial components resulted in antibodies recognizing antigens of 15-200 kDa specific to round spermatids. Together, these findings may contribute to ongoing efforts to identify prominent germ cell antigens for use as diagnostic biomarkers or relevant targets for contraceptive vaccines [39,40].…”
Section: Discussionmentioning
confidence: 94%
“…The ASA have been found to differentially bind to capacitated sperm cells (9,10) and to affect several gamete functions, such as survival and motility (11), acrosomal exocytosis (12)(13)(14), and gamete interaction (15)(16)(17)(18); in addition, evidence suggesting a detrimental effect of ASA on early development of human and mouse embryos has been reported (19)(20)(21). Despite its relevance, the relationship between the presence of ASA and its effect on fertility has remained difficult to establish; this is, at least in part, due to variations in serum concentrations of antibodies in infertile patients (3) as well as to ASA complexity, most likely comprising a vast repertoire of antibodies interacting with multiple sperm components (3,22,23). Although in many cases an impairment of sperm functions has been demonstrated, not all ASA will alter them, because either the antigen is not directly involved in a sperm biologic process or the antibodies do not bind to a functional domain of the antigen, as previously suggested (23).…”
mentioning
confidence: 96%
“…Studies have demonstrated that ASA can interfere with the fertilizing ability of spermatozoa, affecting both sperm motility in the semen and their ability to pass through female genital secretions, the fusion of the gametes (a key event of fertilization), and possibly the first step of embryo development (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%